Integrating Psychopharmacology and Psychotherapy in the Treatment of Mood Disorders: A Comparative Analysis of Combined vs. Standalone Interventions - Hussain, Zeeshan; Iffi, Iffat Imtiaz; Khosa, Rashid Ali (Indus Journal of Bioscience Research, 2025)
Major depressive disorder and bipolar disorder are two common Mood disorders that affect millions of people and cause a lot of disability. Proactive management approaches are crucial when it comes to dealing with symptoms and facilitating a likelihood of healing. Therefore, this study aims at comparing the role of psychopharmacological intervention, psychotherapy, and the combined approach in the treatment of mood disorders. The pharmacological interventions which include antidepressants, mood stabilizers, and antipsychotics are commonly used in psychiatry practice but they are associated with side effects and poor medication compliance. Psychotherapy, especially CBT and IPT have evidence of retention and help with long term benefits but it mandates patient participation and availability. A number of studies conducted in the recent past indicate that combining both pharmacotherapy and talk therapy is beneficial. These participants were those who were going for treatment in Jinnah Postgraduate Medical Centre (JPMC), Karachi hospital, out-patient facilities, and community mental health services. The efficacy analysis of the pharmacotherapy, psychotherapy, or combined treatment for adults includes symptom reduction, rate of relapse, medication compliance in patients, patient satisfaction, and cost-effectiveness of the treatment. The study highlights that integrating these therapies with one another is more effective in eradicating symptoms of depression, decreasing relapse, increasing compliance, and patient satisfaction than simple treatments. Still, there are some challenges which limit provision of integrated treatment, these are financial barriers and accessibility issues. This paper supports the empirical studies emphasizing on patient-centered approach and the policy measures to improve the availability and cost of the combined therapy for mood disorders.